2008
DOI: 10.1080/14786410701424667
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition ofPimpinella anisumL. fruits from various European countries

Abstract: Variations in the essential oil composition of Pimpinella anisum L. fruits obtained from different geographical areas of Europe were determined using capillary GC and GC-MS techniques. The essential oil content of the samples was 10.0-53.6 mL kg(-1) and did not confirm to the European Pharmacopoeia standard in 5 samples out of 14. A total of 21 compounds were identified and significant quantitative differences were observed among the samples. The major component was trans-anethole (76.9-93.7%); the other princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 14 publications
8
78
1
7
Order By: Relevance
“…Interestingly, geijerenes were previously detected in different families such as Asteraceae, Lamiaceae, Rosaceae, Rutaceae and Fabaceae. However, the geijerenes were present only in the Pimpinella genus of the Apiaceae family [41,[42][43][44][45][46]. The stems and leaves, fruit and root essential oil components of S. tripartita confirmed our results that ST-1 oil contained 36.8%, 54.6% and 28.5% geijerene, respectively [17].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, geijerenes were previously detected in different families such as Asteraceae, Lamiaceae, Rosaceae, Rutaceae and Fabaceae. However, the geijerenes were present only in the Pimpinella genus of the Apiaceae family [41,[42][43][44][45][46]. The stems and leaves, fruit and root essential oil components of S. tripartita confirmed our results that ST-1 oil contained 36.8%, 54.6% and 28.5% geijerene, respectively [17].…”
Section: Resultssupporting
confidence: 78%
“…For instance, S. tripartita fruit oil was rich in geijerenes and its root oil contained epoxypseudoisoeugenylangelate and geijerene; which were identified as antibacterial compounds by bioautography method [17]. It is well known that C12 sesquiterpenes (geijerene, pregeijerene) and phenylpropanoids (pseudoisoeugenyl 2-methylbutyrate, epoxypseudoisoeugenyl 2-methylbutyrate) are phytochemical markers for the Pimpinella genera [40][41][42]. In another study, while fruit oil of Scaligeria lazica was found as a rich source of (Z)-β-farnesene (89,2%), the oil of the aerial parts was rich in (E)-anethole (49,7%).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the essential oil of the seeds and leaves of anise consists of 90% t-anethole as well as some methylchavicol, anisaldehyde, and b-caryophyllene (Orav et al, 2008). The close similarity in structure between t-anol and eugenol and isoeugenol suggests that an anise enzyme similar to IGS or EGS might be involved in its synthesis, utilizing the analogous substrate coumaryl acetate.…”
mentioning
confidence: 99%
“…The fungi from genus Fusarium contain zearalenone, fumonisin, moniliformin, fusarin and other toxins (Desjardins, 2006;Frisvad et al, 2006). The quality of anise is determined mainly on the basis of the essential oil content and its composition (Orav et al, 2008). If anise seeds contain mycotoxins, this will be toxic to humans and represents a threat to public health (Jackson and Jablonski, 2004).…”
Section: The Pathogenicity Testmentioning
confidence: 99%